2016
DOI: 10.1002/dev.21445
|View full text |Cite
|
Sign up to set email alerts
|

Training effects and sex difference in preschoolers’ spatial reasoning ability

Abstract: This study examined sex difference in spatial reasoning, a type of spatial cognition necessary for everyday activities. An aggregated data set was composed of data from 273 3- to 4-year olds who participated in 12 different studies using variants of the same spatial reasoning task. This data set was used to investigate whether and how sex difference is related to learning opportunities through training. The results showed that boys outperform girls in general, but this sex difference was influenced by training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
4
5
0
Order By: Relevance
“…The effectiveness of the color strategy is consistent with findings from other spatial reasoning tasks (Diamond et al, 1997;Joh, 2016).…”
Section: G Ener Al Discussionsupporting
confidence: 84%
“…The effectiveness of the color strategy is consistent with findings from other spatial reasoning tasks (Diamond et al, 1997;Joh, 2016).…”
Section: G Ener Al Discussionsupporting
confidence: 84%
“…Exploring a younger population, Levine et al (1999) tested children ranging from 4 to almost 7 years of age on a mental rotation task and found sex differences with boys outperforming girls as early as 4.5 years of age. Sex differences on spatial tasks in 3–4.5 year olds have been replicated in other studies (Levine et al, 2012; Joh, 2016; Pruden and Levine, 2017).…”
Section: Introductionsupporting
confidence: 66%
“…Another longitudinal study (Lachance and Mazzocco, 2006) where over 100 students were followed from kindergarten to third grade to examine sex differences in math and spatial skills found no persistent sex differences during any year of the study, in any area of math or spatial skills, or in growth rates for math or spatial skills. These studies look at change in spatial skills over time in a naturalistic setting, however, none included an analysis of sex differences in change over time in preschool aged children, a time when many children enter formal schooling and sex differences may be emerging (Levine et al, 1999, 2012; Joh, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sex differences in spatial abilities have farreaching consequences in girls' and women's representation in STEM (science, technology, engineering, and mathematics) fields [62]. Previous studies showed that training and engaging in spatial activities improves performance [63].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that training and engaging in spatial activities improves performance [63]. Therefore, early education and training at school should provide learning opportunities to exercise spatial skills [62] through toys and other tangible objects, through abstract problem solving, and other various play opportunities promoting spatial thinking.…”
Section: Discussionmentioning
confidence: 99%